A Bibliometric Analysis of HER2 Positivity as a Predictor of Brain Metastases in Breast Cancer: Insights from VOSviewer - Sakinah Mar'ie Sanad; I Made Oka Adnyana; I Putu Eka Widyadharma (Fakultas Kedokteran Universitas Muslim Indonesia, 2025)
Background: HER2-positive breast cancer (BC) is known for its aggressive behavior and increased risk of brain metastases (BM), which worsens patient prognosis and limits therapeutic options due to the blood brain barrier (BBB). This study systematically evaluates HER2 overexpression as a predictive factor of BM in breast cancer patients through a Systematic Literature Review (SLR) and visualizes global research trends using VOSviewer. Methods: A total of 20 peer-reviewed primary studies published between 2015–2025 were analyzed from PubMed and Scopus databases using the PRISMA framework. Selection was guided by the PICOTS model, and data synthesis included clinical predictors, therapeutic outcomes, and prognostic models. Bibliometric metadata were processed using VOSviewer to explore thematic evolution. Results: HER2 overexpression is consistently linked with earlier BM onset, higher incidence, and distinct survival patterns. Advanced HER2-targeted agents like tucatinib and pyrotinib demonstrated enhanced CNS control. VOSviewer maps revealed five thematic clusters: HER2-targeted therapy, BM prediction models, survival analysis, CNS drug resistance, and HER2-low classification. Conclusion: HER2 positivity is an independent prognostic marker for brain metastases in BC. Its integration into CNS risk stratification and personalized therapy protocols may enhance clinical outcomes in high-risk patients